My first baby animals let's squeak and squawk! - Sirett, Dawn; Lloyd, Clare; Mewati, Gunjan; Moul, Robin (London dorling kindersley, 2022)
This busy board book with tabs gets little ones thinking, talking, and learning new words! Let's meet animals from around the world. What lives at the bottom of the ocean? What are your favourite pets? From mini-beasts to massive mammals, babies and toddlers will love discovering which animals squeak, squawk, and oink!"
Scientific notions
Keywords: Science